A Comparison of the Cyclic Anhydride and Mixed Anhydride Methods for 111In-DTPA Chelation to Monoclonal Antibodies - Wang, T. S. T.; Srivastava, S. C.; Fawwaz, R. A.; Giacomini, P.; Ferrone, S.; Richards, P.; Hardy, M.; Alderson, P. O. (Nuklearmedizin - NuclearMedicine, 1984)
The cyclic anhydride (CA) and the mixed anhydride (MA) of DTPA were synthesized and used to chelate 111In to an antimelanoma monoclonal antibody. The CA and MA methods showed mean labeling efficiencies of 25.7 and 20.5%, respectively (p = NS). The binding efficiency of labeled antibody to human melanoma cells in tissue culture also was similar (x̄ = 52 and 50%, respectively, p = NS), as was tumor uptake in nude mice at 96 hrs post-injection (16%-CA vs 12%-MA). The method required less complicated chemical syntheses, much less preparation time, and the product was stable over a much longer period. The results suggest that the CA method is preferable for bifunctional chelate labeling of monoclonal antibodies with 111In-DTPA.